2016
DOI: 10.5603/kp.a2015.0236
|View full text |Cite
|
Sign up to set email alerts
|

Forced expiratory volume in one second can predict SYNTAX score in patients with chronic obstructive pulmonary disease

Abstract: A b s t r a c t Background:The SYNTAX score is an angiographic score that predicts coronary artery disease (CAD) complexity. It has been shown to be useful for decision making about percutaneous coronary intervention or coronary artery bypass grafting among patients with CAD. Higher SYNTAX scores are indicative of more complex disease. Chronic obstructive pulmonary disease (COPD) is characterised by limitation of airflow. Measurement of forced expiratory volume in one second (FEV1) in spirometry is used for di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
5
0
2
Order By: Relevance
“…Association between multiple vascular disease and COPD has been shown in studies [14,15]. In a study; have been shown that the patients with COPD who underwent PCI procedure had a higher incidence of myocardial injury [14].…”
Section: Discussionmentioning
confidence: 98%
“…Association between multiple vascular disease and COPD has been shown in studies [14,15]. In a study; have been shown that the patients with COPD who underwent PCI procedure had a higher incidence of myocardial injury [14].…”
Section: Discussionmentioning
confidence: 98%
“…Patients with OABSS8 and above has 'overactive bladder' and 16 and above were considered as 'severe symptomatic patients' 15 . The severity of urinary tract symptoms, irritative and obstructive symptoms could be assessed individually by using IPSS 16 .…”
Section: Methodsmentioning
confidence: 99%
“…Chronic obstructive pulmonary disease is a predictor of worse in-hospital survival in those presenting with ACS. 5 8 The COPD cohorts were found to have more severe coronary artery disease on coronary angiography 9 11 and lower utilization of β-blockers, statins, and coronary interventions. 6 8 The guidelines for NSTE-ACS recommend early invasive strategy (EIS), invasive strategy, or ischemia-guided strategy (IGS) based on clinical presentation and high-risk comorbidities (ie, prior coronary artery bypass).…”
Section: Introductionmentioning
confidence: 99%